Pomalidomide alone or in combination with dexamethasone in Japanese patients with refractory or relapsed and refractory multiple myeloma. Issue 11 (4th November 2015) - Matsue, Kosei; Iwasaki, Hiromi; Chou, Takaaki; Tobinai, Kensei; Sunami, Kazutaka; Ogawa, Yoshiaki; Kurihara, Mari; Midorikawa, Shuichi; Zaki, Mohamed; Doerr, Thomas; Iida, Shinsuke
Abstract : This phase 1, open‐label, dose‐escalation study investigated the tolerated dose (recommended dose), safety, efficacy, and pharmacokinetics of pomalidomide alone or pomalidomide plus low‐dose dexamethasone in Japanese patients with refractory or relapsed and refractory multiple myeloma. Twelve patients were enrolled. Patients received pomalidomide 2 mg (Cohort 1) or 4 mg (Cohort 2) orally on day 1 and days 3–21 of a 28‐day cycle. The tolerated dose of pomalidomide was determined to be 4 mg given on days 1–21 of a 28‐day cycle. Efficacy outcomes with pomalidomide plus low‐dose dexamethasone were consistent with those of previous studies. Responses (partial response or better) were achieved by three patients (25%; 1 [17%] in Cohort 1 and 2 [33%] in Cohort 2), and the median time to response was 6.4 months overall (9.0 months for Cohort 1 and 4.2 months for Cohort 2). The median progression‐free survival was 5.5 months overall (5.1 months for Cohort 1 and not reached for Cohort 2). The most frequently occurring grade ≥3 adverse events were neutropenia (67%), anemia (25%), lymphopenia (25%), and pneumonia (25%), consistent with previous studies of pomalidomide plus low‐dose dexamethasone in refractory or relapsed and refractory multiple myeloma. Further investigation of pomalidomide is recommended for Japanese patients with refractory or relapsed and refractory multiple myeloma. This study was registered with ClinicalTrials.gov (NCT01568294). Abstract : This phase 1, open‐label, dose‐escalation study in Japanese patients with refractory or relapsed and refractory multiple myeloma investigated the tolerated dose (TD; recommended dose), safety, efficacy, and pharmacokinetics of single‐agent pomalidomide or pomalidomide plus low‐dose dexamethasone. The TD was found to be pomalidomide 4 mg days 1–21 of a 28‐day cycle. Pomalidomide plus low‐dose dexamethasone demonstrated efficacy in this patient population (median progression‐free survival = 5.5 months) and the safety profile was consistent with prior studies of pomalidomide.